Slope Stability Analysis for Optimization of Coal Blocks 7-12, Seam H Pit T4U, Sambarata Mine Operation, PT Berau Coal Based on Mohr-Coulomb Failure Criterion - Erlangga Adi Nugroho; Yuzar Chairil Firmansyah; Lukman Hakim (PERHAPI, 2022)
Mine planning is the process of determining mine design and operational activities carried out to determine the feasibility of mine design and operational activities. Mining design certainly requires slope stability analysis to ensure the safety and security of mining operations and the resource itself. Differences between mine design and actual conditions in the field can occur at any time, such as coal optimization. This coal optimization can be done but still have to pay attention to the slope stability. There are several methods to analyze slope stability, such as the limit equilibrium method which is based on the Mohr-Coulomb failure. This method is a slope stability analysis method used to determine the response of rock material to the forces acting on the material. This method is the method used to conduct slope stability analysis for optimization of blocks 7-12, seam H Pit T4U, Sambarata Mine Operation, PT Berau Coal. In addition to slope stability analysis, monitoring using Slope Stability Radar (SSR) is also needed to monitor deformation in the area. Optimization is carried out to increase the amount of coal production but by still paying attention to the safety factor of the slopes. Optimization is done by adding a decrease in elevation whereas, in the initial planning, mining activities are only carried out up to an elevation of (-60) mRL . After optimization, mining activities can be continued up to an elevation of (-70) mRL. Based on data on production targets in block 7-12, seam H, Pit T4U, the target of coal production at that block is 445 metric tons (MT) and after optimization, coal production at that block increased by 44.9% to 645 MT. Based on the geotechnical analysis, this optimization can be carried out. However, in practice, monitoring of mining activities is necessary and monitoring is required through Slope Stability Radar (SSR) monitoring to monitor deformation, especially in the high wall area to anticipate material movement.